Comparative Analysis of Phenolic, Flavonoid, and Antioxidant Activity in Green, Black, and White Tea Kombucha - Suantari, Ni Gusti Ayu Made Dewi; Purwanto, Ukhradiya Magharaniq Safira; Safithri, Mega (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2025)
This research explored how varying tea substrates (green, black, and white) affected the phenolic content, flavonoid content, and antioxidant activity of kombucha fermented with SCOBY. Four samples were prepared, including a control (no tea) and kombucha made from green, black, and white tea bases. The results showed that black tea kombucha had the highest levels of antioxidant compounds and activity. The DPPH assay revealed that black tea kombucha exhibited the highest antioxidant activity; a percent inhibition of 88.285 ± 2.196% and an IC50 value of 30.835 ± 1.340 µL/ml. Additionally, black tea kombucha had the highest total phenolic content (921.282 ± 38.075 mg GAE/L) and total flavonoid content (421.818 ± 24.052 mg QE/L). The type of tea used significantly impacted the final total phenolic content, total flavonoid content, and overall antioxidant activity of the resulting kombucha. Furthermore, the fermentation process also led to consistent decreases in pH and density across all samples. These comparative data offer valuable insight for optimizing tea-based kombucha formulations for functional food and beverage applications.